Progression of liver fibrosis in pulmonary arterial hypertension. (14th October 2021) - Goten, C; Usui, S; Okada, H; Inoue, O; Takashima, S; Sakata, K; Kawashiri, M; Takamura, M
Abstract: Background: Pulmonary arterial hypertension (PAH) causes congestive liver due to right heart failure. There are few cases of PAH that lead to liver cirrhosis, and little attention is paid to liver function in PAH patients. However, it is certain that long-term congestion due to right heart failure in PAH causes a gradual exacerbation of liver dysfunction and affects metabolic function. Purpose: The purpose of this study is to investigate liver fibrosis associated with the severity and prognosis of PAH. Methods: This retrospective observational study was included 57 PAH patients and 22 control subjects. PAH patients were assigned to three risk variables according to the simplified risk stratification proposed at the 6thWSPH 2018 after measuring hemodynamic parameters using right heart catheterization, WHO functional class, 6- minutes walking distance (6MWD), and BNP plasma levels. The Fibrosis-4 (FIB4)-index, a liver fibrosis marker, was calculated using the formula: FIB-4 = Age (years) × AST (U/L) / [PLT (10 9 /L) × ALT1/2 (U/L)], and assessed for association with severity of PAH. PAH patients were followed up for 12 years to assess the occurrence of major adverse event, such as death or lung transplantation. Next, adult 8-week-old C57BL/6 mice were exposed to chronic hypoxia (10% O2) or normoxia for 6 weeks. Then, mice were anesthetized and performed right heart catheterization. Liver tissue was collected for histological assessment by Hematoxylin and eosin and Azan staining, and evaluated RNA expression involved in liver fibrosis by real-time PCR. Results: The levels of FIB4-index in intermediate and high risk groups of PAH patients had significantly increased compared to those in control group. In PAH patients, FIB4-index was not obviously correlated with hemodynamic parameters, BNP, or 6MWD. Major adverse events occurred in 18 PAH patients (32%): death in 18 (100%) and lung transplant in none (0%). Kaplan-Meier curves for PAH patients with and without major adverse events were constructed based on a cut-off frequency of 2.001 for FIB4-index. During the 12-years follow-up period, major-event-free survival was significantly better in PAH patients with FIB4-index <2.001 than in patients with FIB4-index >2.001 (hazard ratio, 3.3; P=0.038). In a PAH model mice, hemodynamic parameters showed that chronic hypoxia significantly increased the right ventricular systolic pressure. In histological analysis, there was no significantly difference in liver fibrosis in hypoxia or normoxia group. However, the RNA expression such as αSMA and TGFβ1 associated with liver fibrosis in PAH model mice was increased compared to control mice. Conclusion: This study showed that the liver fibrosis gradually progressed subsurfacely with severity of PAH. Even the slight liver dysfunction may affect metabolism and cause exacerbation of PAH, so it might be necessary to pay attention to liver fibrosis as one of the risk factors of PAH. FUNDunding Acknowledgement: Type of funding sources: None.